Genetically engineered animal models for Marfan syndrome: challenges associated with the generation of pig models for diseases caused by haploinsufficiency - Naomi JACK; Tomoyuki MUTO; Keigo IEMITSU; Tamaki WATANABE; Kazuhiro UMEYAMA; Jun OHGANE; Hiroshi NAGASHIMA (The Society for Reproduction and Development, 2022)
Recent developments in reproductive biology have enabled the generation of genetically engineered pigs as models for inherited human diseases. Although a variety of such models for monogenic diseases are currently available, reproduction of human diseases caused by haploinsufficiency remains a major challenge. The present study compares the phenotypes of mouse and pig models of Marfan syndrome (MFS), with a special focus on the expressivity and penetrance of associated symptoms. Furthermore, investigation of the gene regulation mechanisms associated with haploinsufficiency will be of immense utility in developing faithful MFS pig models.